A Semianalytical Solution for Passively Loaded Piles Adjacent to Surcharge Load. (10th June 2020) - Zhang, Hao; Shi, Minglei; Yang, Lei; Guo, Yuancheng
Abstract : Piles adjacent to a surcharge load commonly support not only active loads from superstructures but also the passive loads caused by soil lateral movement. To investigate the influence of passive load and the response along pile shafts of existing actively loaded piles, a load transfer model for analyzing the soil-pile interaction was developed based on plastic deformation theory and the triparameter soil model. An analytical solution for the deformation and internal force of such piles was proposed using the transfer matrix method, in which the transfer matrix coefficients for piles in free, plastic, and elastic zones were analytically obtained by considering the second-order axial force effect caused by lateral loading and soil yielding based on the triparameter soil model. The proposed methodology was validated by comparing its predictions with field measurements and previously published results. A good match between model predictions, field measurements, and previously published results implies that the proposed method can be used to evaluate the response of passive piles adjacent to a surcharge load. Parametric studies were also carried out to investigate the influence of surcharge pressure, soil resistance, and boundary conditions on the behavior of passively loaded piles adjacent to a surcharge load.